AN ANALYSIS OF MANAGEMENT ACCOUNTING INFORMATION SYSTEMS, HUMAN CAPITAL, AND LEADERSHIP STYLE TO IMPROVE MANAGERIAL PERFORMANCE AT PT. MITRA NUR JAYA SEJATI - Ivan Prasetyo Karyow; Hadiah Fitriyah (PT ANTIS INTERNATIONAL PUBLISHER, 2026)
Objective: Increasingly intense business competition demands that every company continually improve efficiency, productivity, and service quality to survive and grow. The success of an organization is greatly determined by good managerial performance, which is supported by three main factors: the implementation of management accounting information systems, the management of human resources or human capital, and the application of an appropriate leadership style. This research was conducted at PT Mitra Nur Jaya Sejati, which operates in the field of providing external workforce or outsourcing services, to analyze the role of these three factors in supporting the improvement of the company's managerial performance. Method: The method used in this research is a qualitative method with a descriptive approach, where data is collected and described to depict the actual conditions occurring in the field. Results: The research results show that the management accounting information system plays a role in providing accurate, timely, and quality information that serves as the basis for planning, decision-making, and monitoring company activities. Human capital management is implemented through the provision of continuous training programs, mapping of employee potential, and the preparation of clear career paths, thereby enhancing skills and work motivation. In addition, the leadership style applied also plays a role in maintaining work spirit, building team cooperation, and creating a conducive work environment. Overall, these three factors have a significant influence on managerial performance. Novelty: This research is expected to provide benefits to companies as a consideration in formulating business development strategies and serve as a reference for future research.